Effect of hepatitis B virus subgenotype on antiviral response in nucleoside‐treated hepatitis B envelope antigen‐positive patients. Issue 2 (6th June 2017) - Shen, Sheng; Liang, Xieer; Hamed, Kamal; Tanaka, Yasuhito; Omagari, Katsumi; Fan, Rong; Xie, Qing; Tan, Deming; Zhou, Bin; Jia, Ji‐Dong; Hou, Jinlin; Sun, Jian
Abstract : Aim: Previous studies have reported that hepatitis B virus (HBV) genotype is not a predictor of treatment response with nucleos(t)ide analog therapy. However, the impact of subgenotype on treatment response is unknown. The aim of this study is to identify the effect of HBV subgenotype on treatment response. Methods: In this retrospective study, the derivation dataset comprised patients from the EFFORT study (NCT00962533) telbivudine monotherapy group; patients infected with genotypes B or C from the GLOBE (NCT00057265) and 015 (NCT00131742) studies formed the validation dataset. The HBV subgenotypes were determined using phylogenetic analysis based on the surface or overlapping polymerase gene. Molecular modeling was used to investigate relationships between positions of the substitutions within reverse transcriptase and genotypic resistance. Results: Of the patients in the derivation dataset, 110, 24, 162, and 1 patients were classified as having HBV subgenotypes B2, C1, C2, or other, respectively, compared to 222, 146, 282, and 51 in the validation dataset, respectively. Patients infected with subgenotype C1 showed a higher virologic response rate and hepatitis B envelope antigen seroconversion rate, and lower genotypic resistance rate than those infected with subgenotypes B2 and C2. Patients with genotypic resistance to telbivudine with subgenotype C1 showed fewer secondary mutations. The crystal structure model of reverse transcriptase showed that these secondary mutations were located around the YMDD motif, which possibly influenced the chance of mutations at rtM204. Conclusion: Hepatitis B virus subgenotype C1 is associated with better antiviral response to nucleoside analogs in hepatitis B envelope antigen‐positive patients than B2 and C2 subgenotypes. The exact mechanism needs to be explored further.